Canva Genius Workshop 2025: empowering students with creativity and digital skills - Mohd Ruslan, Siti Zaharah; Othman, Norlida; Rosli, Nur Aqilah Balqis; Abdul’s-Salam, Orkid Afrina (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The Canva Genius Workshop 2025, organized by the Cybermath Club at UiTM Negeri Sembilan, Kuala Pilah Campus, was held on 15 June 2025 at Dewan Sri Perpatih with 19 student participants and 16 committee members under the guidance of two academic advisors. The workshop provided hands-on exposure to Canva, a popular digital design tool, aiming to enhance students’ creativity, digital competency, and presentation design skills. Participants gained practical experience in creating academic posters, infographics, and professional slide presentations, while building confidence in using Canva for academic and professional purposes.